Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4149/gpb_2018008
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the ABCB1 drug transporter in acute myeloid leukemia cells is associated with downregulation of latrophilin-1

Abstract: Finding new markers with appropriate prognostic levels for the differential diagnosis of neoplastic diseases represents an important issue for biomedical research. Recently, latrophilin-1 (LPHN1) was reported to be expressed in human monocytic leukemia cell lines and in primary human acute myeloid leukemia (AML) cells. However, this expression was found to be absent in healthy leukocytes. LPHN1 was therefore considered a novel biomarker of human AML. In previous papers, we established two P-gp-positive variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…Consistent with our previous results [ 30 ], massive ABCB1 gene expression was detected only in the resistant sublines (SKM-1/VCR and MOLM-13/VCR) by either RT-PCR or qRT-PCR ( Figure S3 in supplementary files ). ABCB1 protein was also identified by Western blot exclusively in SKM-1/VCR and MOLM-13/VCR cell variants and not in the parental SKM-1 and MOLM-13 cells ( Figure S3 in the supplementary files ).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with our previous results [ 30 ], massive ABCB1 gene expression was detected only in the resistant sublines (SKM-1/VCR and MOLM-13/VCR) by either RT-PCR or qRT-PCR ( Figure S3 in supplementary files ). ABCB1 protein was also identified by Western blot exclusively in SKM-1/VCR and MOLM-13/VCR cell variants and not in the parental SKM-1 and MOLM-13 cells ( Figure S3 in the supplementary files ).…”
Section: Resultssupporting
confidence: 92%
“…The presence of latrophilin-1 has been observed in the plasma membrane of myeloid leukemia blasts from patients with AML but not in healthy mature leukocytes [ 26 ]. We also verified the presence of this protein in the AML lines MOLM-13 and SKM-1 [ 30 ]. However, we found that latrophilin-1 was downregulated in ABCB1-positive MOLM-13/VCR and SKM-1/VCR variants.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations